Spektrum Gstar(1;1) - Nunung Nurhayati; Udjianna Sekteria Pasaribu; Dudung Muhally Hakim; Oki Neswan (Institut Teknologi Bandung, 2008)
In this paper we formulate the spectrum (spectral density matrix) of the stationary GSTAR(1;1) model by considering the model as VMA( â). The spectrum can be obtained by following steps: represent the model as an VMA( â) and convert the model to the backward operator form, then substitute the coefficient model to the spectrum of VMA( â) model. The procedure of finding spectrum of GSTAR(1;1) which parameters are given, is illustrated by a two dimensional GSTAR(1;1) model.